PENDAMPINGAN TEKNOLOGI TEPAT GUNA MESIN PENCUCI EMPON-EMPON DI CV. DIPA KUNCARA, DRIYOREJO GRESIK - Tukiran Tukiran; Yunus Yunus; Woro Setyarsih; Rizdana Galih Pambudi; Cindy Ambarwati; Handini Zahrah Firdausi; Anjani Fadia Putri (Universitas Negeri Surabaya, 2026)
The herbal washing process at CV. Dipa Kuncara, Driyorejo, Gresik, is still carried out manually, namely washing fresh and dirty herbal ingredients weighing around 5-6 kg into a basin filled with around 10 L of water, brushing, and rinsing/sprayed with running water up to 3-4 times. One washing session takes around 40-50 minutes to remove dirt and other things. In addition, stirring and washing herbal ingredients that still contain a lot of soil and dirt is often very tiring. On the other hand, manual washing of herbal ingredients also results in very low stability of the quality of herbal medicines. This can cause the resulting herbal products to have a less fresh taste and a slightly unpleasant odor. The solution offered in this PKM activity is the need to prepare a Herbal Washing Machine. The purpose of this community service is to assist MSMEs in the process of washing ingredients/initial materials by building a herbal washing machine. The methods and stages of community service activities include: 1) preparing herbal washing machines and testing them, 2) providing operational assistance for tools/machines to partners, 3) monitoring and evaluating the use of tools/machines, and 4) distributing questionnaires for all PKM implementations. The results: 1) herbal washing tools/machines have been made, 2) partners are able and skilled at using the tools/machines, 3) monitoring and evaluation results report that partners have used the herbal washing tools/machines well, routinely and no longer do it manually, and 4) partners feel satisfied and happy with all the PKM training and assistance provided by the implementation team. By using this tool/machine, the process time can be saved up to 10–15 minutes for one washing-to-rinsing process, herbal products become fresher and odorless, and of course, will produce clean and healthy instant herbal powder products.